Endoscopic Ultrasound–guided Drainage of Walled-off Necrosis in Children With Fully Covered Self-expanding Metal Stents. Issue 4 (April 2017) - Nabi, Zaheer; Lakhtakia, Sundeep; Basha, Jahangeer; Chavan, Radhika; Ramchandani, Mohan; Gupta, Rajesh; Kalapala, Rakesh; Darisetty, Santosh; Talukdar, Rupjyoti; Reddy, Duvuur Nageshwar
ABSTRACT: Objectives: Endoscopic ultrasound (EUS)-guided drainage with fully covered self-expanding metallic stents (FCSEMS) has been successfully used in adult patients. The utility of FCSEMS in children with walled-off necrosis (WON) is, however, unknown. The aim of present study was to evaluate the feasibility, safety, and efficacy of EUS drainage of WON using FCSEMS in children. Methods: We retrospectively evaluated the data of children (18 years or younger) who underwent EUS drainage of WON using FCSEMS at our institution. All FCSEMS were removed between 1 and 3 months. Feasibility, safety, and efficacy were analysed. Results: Twenty-one children (20 boys, mean age 14.9 ± 2.34 years, range 9–18 years) underwent EUS-guided drainage of WON with FCSEMS. The median size of WON was 88 mm (55–148 mm). The median interval between onset of acute pancreatitis and EUS guided drainage was 58 days (range 30–288 days). The technical and clinical success rates were 100% and 95%, respectively. Nasocystic tube was placed in 3 children for lavage. Endoscopic necrosectomy was not required in any of the children. There were no major complications. Minor complications included bleeding (2), stent migration (1), and difficulty in removal of stent (1). After a median follow-up of 360 days (range: 30–1020 days), there was 1 recurrence of WON. Conclusions: EUS drainage of WON using specially designed FCSEMS is safe and efficacious in children. The utility of FCSEMS in children should be further explored and compared with plastic stents. Abstract : Supplemental Digital Content is available in the text